Exploring the impact of a Volunteer Shared Reading Programme on preschool-aged children. Issue 6 (3rd June 2018) - Fitzgerald, Tamara; Robillard, Laurance; O'Grady, Amy
ABSTRACT: Shared reading interventions that target children at risk of developmental delays or those from low-income homes have been successful in improving children's emergent literacy skills. Interventions that are implemented in childcare or education settings have also been shown to improve children's emergent literacy; however, implementation of shared and dialogic reading programmes can be difficult in childcare environments where one-on-one time is limited. Hence, shared reading interventions that elicit the help of volunteers from the community are an ideal alternative. The current study examined the effects of a volunteer-implemented dialogic reading intervention on 75 children aged from three to five years, focusing on measures of vocabulary, oral comprehension, print awareness, social–emotional behaviour, communication skills, and book reading tendencies. Results showed significant improvements across all outcome variables, supporting the viability of volunteer-implemented reading interventions in childcare settings for improving children's emergent literacy, communication and social–emotional behaviour.